Breeding performance of an Irish Mute Swan Cygnus olor population - Collins, Richard (Wildfowl, 2013)
Mute Swans breeding in Dublin, Ireland were studied from 1983 to 1989. Only 46% of birds bred in the season in which they were five years old. The mean clutch size was 6.7. About 80% of clutches hatched. The mean brood size was 4.2 per nest at hatching and 2.7 per 'nest’ at the age of three months. A shortage of suitable territories seemed to limit recruitment to the breeding population and to promote the use of inadequate territories, especially on estuaries, in (usually futile) breeding attempts. Urban breeders tended to be younger than rural ones.